A study on thermal-induced distortion in solid objects - Cao, Yangfeng (2008)
The thermal-induced distortions in three simple-shaped solids that are a cube, a short cylinder and a sphere loaded with temperature boundary conditons are studied. Lastly focus is made on our main concern for a slider head.